Charge transfer induced activity of graphene for oxygen reduction. (23rd March 2016) - Shen, Anli; Xia, Weijun; Zhang, Lipeng; Dou, Shuo; Xia, Zhenhai; Wang, Shuangyin
Abstract: Tetracyanoethylene (TCNE), with its strong electron-accepting ability, was used to dope graphene as a metal-free electrocatalyst for the oxygen reduction reaction (ORR). The charge transfer process was observed from graphene to TCNE by x-ray photoelectron spectroscopy and Raman characterizations. Our density functional theory calculations found that the charge transfer behavior led to an enhancement of the electrocatalytic activity for the ORR.